Neurological Sequelae in Acute Encephalitis Syndrome one month post discharge from the hospital in the Children Aged 1-14 years - Giri, Arun; Sah, Vijay Kumar; Sedhain, Raju; Chimoriya, Romia (Journal of Nobel Medical College, 2016)
Introduction Encephalitis is a complex clinical syndrome of the central nervous system (CNS) associated with fatal outcome or severe permanent damage including cognitive impairment, behavioral impairment and epileptic seizures. It is important to understand the clinical spectrum and outcome of acute encephalitis syndrome(AES) at local level to better define problem and to draw inferences for management and policy formulation.Material and Methods: This study was a hospital based observational, longitudinal and descriptive study conducted at Department of Pediatrics; Nobel Medical College Teaching Hospital, Biratnagar. Seventy cases with a diagnosis of AES (irrespective of the underlying etiology), were studied over a period of one year. All cases from 1 to 14 years of age fulfilling the standard WHO case definition of AES were included in the study. A pre-designed semistructured questionnaire was being used to obtain the clinical profile and investigations. The cases were followed after one month post discharge from the hospital and the outcomes were recorded.Results: On follow up of the cases at the end of 1 month, 35 (50.7%) cases were found to have complete cure and were labelled as cured. Neurological sequelae were seen in 8(11.6%) cases and were labeled as not cured. Total death was documented in 26(37.7%) of the cases.Conclusion: Despite of early diagnosis and aggressive treatment neurological sequelae is not uncommon in AES. So, regular follow up and early rehabilitative efforts should be instituted for all cases of AES post discharge from the hospital.Journal of Nobel Medical College Vol.5(2) 2016; 43-46